The effectiveness of Employees Provident Fund Social Security Training Institute (ESSET) as the training centre for employees / Saiful Bakhtiar Nasruddin - Nasruddin, Saiful Bakhtiar (Faculty of Business and Management, 2007)
This study will focus on measuring on the effectiveness of Employees Provident Fund Social Security Training Institute (ESSET) by focusing on customer satisfaction. This study was conducted at Employees Provident Fund (EPF) Headquarter at Jalan Raja Laut, Kuala Lumpur where the focused respondent were the EPF employees itself who using Employees Provident Fund Social Security Training Institute (ESSET) facilities and services. The dependent variable for this study is customer satisfaction, while the independent variable are facilities provided, management or personnel and variety of program or courses offered by Employees Provident Fund Social Security Training Institute (ESSET). The respondents have been choosing by using Simple Random Sampling method and the random process are doing by using lottery method. This objective are regarding to facilities provided by Employees Provident Fund Social Security Training Institute (ESSET), management and personnel at Employees Provident Fund Social Security Training Institute (ESSET) and training and courses provided by Employees Provident Fund Social Security Training Institute (ESSET). For this purpose, the data that has been collected through questionnaire will be analyzed using Statistical Package for Social Science program (SPSS) to ensure analysis on data frequencies. After conducted this research, researcher found that most of the respondents are satisfied with the training, courses and all facilities provided by Employees Provident Fund Social Security Training Institute (ESSET) but the Employees Provident Fund Social Security Training Institute (ESSET) management must improve certain factors to make sure their customer satisfaction level increasing in future.